The Plastid-Localized AtFtsHi3 Pseudo-Protease of Arabidopsis thaliana Has an Impact on Plant Growth and Drought Tolerance - Mishra, Laxmi S.; Mishra, Sanatkumar; Caddell, Daniel F.; Coleman-Derr, Devin; Funk, Christiane (Frontiers in Plant Science, 2021)
While drought severely affects plant growth and crop production, the molecular mechanisms of the plant´s drought response remain unclear. Here we demonstrate for the first time the pseudo-protease AtFtsHi3 of Arabidopsis thaliana to affect overall plant growth and to be involved in drought tolerance. An AtFTSHi3 knock-down mutant (ftshi3-1(kd)) displayed a pale-green phenotype with lower photosynthetic efficiency and Darwinian fitness compared to Wt. An observed delay in seed germination of ftshi3-1(kd) was attributed to over-accumulation of ABA; ftshi3-1 (kd) seedlings showed partial sensitivity to exogenous ABA. Being exposed to similar severity of soil drying ftshi3-1(kd) was drought-tolerant up to 20-days after the last irrigation, while wild-type plants wilted after 12 days. Leaves of ftshi3-1(kd) contained reduced stomata size, density and a smaller stomatic aperture. During drought stress, ftshi3-1(kd) showed lowered stomatal conductance, increased intrinsic water-use efficiency and slower stress acclimation. Expression levels of ABA-responsive genes were higher in leaves of ftshi3-1(kd) than wild type; DREB1A, but not DREB2A, was significantly upregulated during drought. However, although ftshi3-1(kd) displayed a drought-tolerant phenotype in aboveground tissue, the root-associated bacterial community responded to drought.